Application of psychological work sheets experiments and non experiments on environmental pollution meters to improve learning outcomes and skills process science of high school students Trienggadeng - Siska Yani; Hafnati Rahmatan; M Ali S (Jurnal Edubio Tropika, 2018)
This study aims to determine differences in learning results on environmental pollution materials after Work Sheets Experiments. Data retrieval was conducted in March 2017. The method used in this researchis quasi experimental method. This research was conducted at SMA and MA of Trienggadeng Sub-district with sample of 42 students in every school. The instrument used is a test to assess learners' learning outcomes. Data analysis used indepenent sample t-test at significant level 0,05. The results showed that thitung ttable is tcount 5,45 ttable 1,98. Conclusion there are differences in student learning outcomes applied Work Sheets Experiments and non experiments on environmental pollution materials in high school students Trienggadeng District Pidie Jaya District.Keywords: LKPD Experiments and Learning Outcomes.